Analisis Studi Kelayakan Pengembangan Usaha Pakaian Wanita Pada Usaha Risya Fashion Muara Bulian - Siti Marlina; Reni Setiawati (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2020)
This study aims to determine the amount of investment and working capital, determine the condition of the aspect of the feasibility study, and determine the feasibility of the business assessed from the investment criteria on development Of Effort Women clothes Risya Fashion in jalan Baru Talang Inuman. In this research, the analytical method used is descriptive qualitative analysis method, which is a method used to measure the feasibility of a business in women clothing business measurement of quantitative data through calculation of investment data to measure business feasibility.As for expense of Invesment and Working capital required for the Development Of Effort Women clothes Risya Fashion in jalan Baru Talang Inuman this equal to Rp. 184.248.500. Source of - source of this fund cover capital alone equal to Rp. 84.248.500 and Bank loan equal to Rp. 100.000.000 with rate of interest 12%. From overall of used aspect development of this Effort, that is Aspect law, Environmental aspect, Aspect Market and marketing, technological and Technical aspect, Management aspect and of resource human being, Monetary aspect which required in development of Effort Development Of Women clothes Risya Fashion in jalan Baru Talang Inuman competent to be developed. While plan development of the effort studied by 5 invesment criterion method that is with method of Net Present Value ( NPV ) equal to Rp. 129,536,531.70is, Internal Rate Of Return ( IRR ) equal to 55.51 %, Net Benefit Cost Ratio ( Net B / c ) equal to 1,5375, Gross of Benefit Cost Ratio ( Gross of B / c ) equal to 1,1057and Break Even Point ( BEP ) showing needed to time close over nvestment equal to Rp. 184.248.500, is during 4 year 6 months 22 day.